Peran Badan Usaha Milik Desa Bagi Masyarakat Desa (Perspektif Maqashid Syariah) - Ratna Sari Dewi; Ova Novi Irama (AGHNIYA : Jurnal Ekonomi Islam, 2020)
The purpose of this study is to determine the extent of the role of BUMDes in the community based on the perspective of Islamic maqashid. This type of research is a qualitative descriptive study. The subject of this research is Helvetia Makmur Berdikari Village and the object of this research is BUMDes financial report data. The data analysis technique of this study was by analyzing the results of BUMDes financial statements and also conducting in-depth interviews with village officials. The results of this study indicate that the BUMDes has provided benefits to the village community. The benefits provided in sharia maqashid are in terms of assets.